2013
DOI: 10.3329/ijpls.v2i3.15455
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Reversed-Phase HPLC Method for the Determination of Vildagliptin from Tablet Dosage Form

Abstract: A simple, rapid, precise and cost effective method has been developed and validated for determination of Vildagliptin in pharmaceutical tablet dosage form. The chromatographic separation was carried out with Shimpack VP-ODS, 150 × 4.6 mm, 5µm analytical column and mobile phase containing 0.02M phosphate buffer (pH 4.6) and acetonitrile at the ratio (80:20% v/v). pH of the buffer solution was adjusted with orthophosphoric acid. The instrumental settings include flow rate 0.7 ml/min, column temperature at 25ºC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The results indicated that there is no significant variation between the proposed methods and the reference method with respect to accuracy and precision. [23]; 10, 11 reference method [30]; 18 reference method [54], 19 reference method [55], 20, 22 reference method [56].…”
Section: Application Of the Methods To Pharmaceutical Formulationsmentioning
confidence: 99%
“…The results indicated that there is no significant variation between the proposed methods and the reference method with respect to accuracy and precision. [23]; 10, 11 reference method [30]; 18 reference method [54], 19 reference method [55], 20, 22 reference method [56].…”
Section: Application Of the Methods To Pharmaceutical Formulationsmentioning
confidence: 99%
“…The market is flooded with many drugs for the management of diabetes and it is also prime requirement to have quality medicines a patient have to get relief from increase glucose level. Several methods available to estimate Vildagliptin (VIL) and Dapagliflogin (DAP) by using UV Spectroscopy [1][2][3][4][5], UPLC [6], RP-HPLC [7][8][9][10][11][12][13], UPLC and LC-MS/MS [14][15][16] in individual dosage form and combination with Metformin and Saxagliptin. In the current scenario, regulatory authority also recommend manufacturer to have quantitative and qualitative estimation by sophisticated instrument HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The market is ooded with many drugs for the management of diabetes and it is also prime requirement to have quality medicines a patient have to get relief from increase glucose level. Several methods available to estimate Vildagliptin (VIL) and Dapagli ogin (DAP) by using UV Spectroscopy [1][2][3][4][5], UPLC [6], RP-HPLC [7][8][9][10][11][12][13], UPLC and LC-MS/MS [14][15][16] in individual dosage form and combination with Metformin and Saxagliptin. But, no single method was available for simultaneous determination and stability indicating assay method of VIL and DAP by RP HPLC.…”
Section: Introductionmentioning
confidence: 99%